2013
DOI: 10.1080/01634372.2013.773392
|View full text |Cite
|
Sign up to set email alerts
|

Older Women Doing Home Care: Exploitation or Ideal Job?

Abstract: The increased need for both personal assistance workers and meaningful employment opportunities for older workers results in growing numbers of older home care aides. This study examined lifetime financial security and perceived advantages of older age in this field through interviews with 31 older home care aides. Study participants experienced high levels of financial insecurity and perceived older workers as particularly well suited to the home care job. The consequences of this low-wage, low-status work ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…Although home care work carries positive aspects, such as the opportunity to care and support older adults (Butler, 2013; Shinan-Altman, Riabzev, & Ayalon, 2018), research has indicated that providing home care to older adults is a difficult physical and mental work. It often requires looking after older adults and providing assistance in performing basic ADL such as bathing, dressing, and feeding (Kelly, Morgan, & Jason, 2017) as well as doing light household work such as cleaning and cooking.…”
Section: Home Care Workersmentioning
confidence: 99%
“…Although home care work carries positive aspects, such as the opportunity to care and support older adults (Butler, 2013; Shinan-Altman, Riabzev, & Ayalon, 2018), research has indicated that providing home care to older adults is a difficult physical and mental work. It often requires looking after older adults and providing assistance in performing basic ADL such as bathing, dressing, and feeding (Kelly, Morgan, & Jason, 2017) as well as doing light household work such as cleaning and cooking.…”
Section: Home Care Workersmentioning
confidence: 99%
“…We then turn to two vulnerable populations. Sandra S. Butler (2013) reports on her study of older workers doing jobs in home care, noting the paradoxical quality of this low-wage employment that offers older workers the opportunity for meaningful work while at the same time exposing them to exploitive conditions. Then Keith A. Anderson and colleagues (2013) reflect on factors that serve barriers and supports to the employment of low-income older adults.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Como o envelhecimento é inerente ao ser humano, o cuidador também envelhece, e presta cuidados a pessoas, em sua maioria, também idosas 8 . Estes, em situação de vulnerabilidade, estresse e isolamento social 9-11 . Portanto, como resultado das repercussões do cuidado e do estado de vulnerabilidade do idoso cuidador há desencadeamento de eventos desgastantes de características físicas epsicossociais, podendo gerarmal-estar e tensão podendo ser suprimidopor meio de estratégias de enfrentamento ou coping.…”
Section: Introductionunclassified